Governance, Risk Management, and Compliance as Organizational Capabilities for Sustainable Halal Certification Implementation: Evidence from Indonesian Food and Beverage MSMEs (West Science Journal Economic and Entrepreneurship, 2026)
Halal certification research has predominantly examined awareness, knowledge, adoption intention, consumer responses, or downstream business outcomes. Less is known about the organizational capabilities that enable micro, small, and medium enterprises (MSMEs) to sustain halal requirements after certification enters day-to-day operations. This study investigates governance, risk management, and compliance (GRC) as distinct but complementary organizational capabilities influencing halal certification implementation among food and beverage MSMEs in Greater Jakarta (Jabodetabek), Indonesia. Institutional Theory is used to explain why firms respond to regulatory and normative pressures, while the GRC perspective explains how those pressures are translated into internal managerial mechanisms. A quantitative, explanatory, cross-sectional survey was conducted with 200 MSME owners or managers selected through purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4. Following measurement-model purification, the final model demonstrated satisfactory reliability, convergent validity, and discriminant validity. The structural model explained 78.9% of the variance in halal certification implementation (R² = 0.789; adjusted R² = 0.785), with predictive relevance (Q² = 0.783) and good model fit (SRMR = 0.041). Governance (β = 0.341, t = 6.692, p < 0.001), risk management (β = 0.379, t = 7.999, p < 0.001), and compliance (β = 0.321, t = 7.439, p < 0.001) all exerted positive and significant effects. Risk management was the strongest predictor. The study contributes by reframing halal certification implementation from a predominantly administrative-compliance issue into an organizational-capability problem. It argues that Institutional Theory explains why MSMEs respond to external halal pressures, whereas GRC explains how those responses are operationalized internally through direction and accountability, anticipation and control, and regulatory alignment. The findings imply that certification programs should extend beyond application assistance toward post-certification governance, halal risk management, and continuous compliance capability.